Portland cement clinker production using concentrated solar energy – A proof-of-concept approach. (1st May 2019) - Oliveira, F.A. Costa; Fernandes, J.C.; Galindo, J.; Rodríguez, J.; Cañadas, I.; Vermelhudo, V.; Nunes, A.; Rosa, L.G.
Graphical abstract: Highlights: Synthesis of Portland clinker by concentrated solar energy was fortunately achieved. The reactivity of the raw mix is very sensitive to clinkerization time. Reliable surface temperature control during clinkerization was demonstrated. Controlled cooling at suitable rate is essential for attaining the desired phases. White clinker is hard to produce owing to its low solar absorptance. Abstract: The aim of this work was to demonstrate the feasibility of producing Portland cement clinker upon direct exposure of the raw materials under concentrated solar radiation using the PSA high concentration solar furnace SF40. For this purpose, a short thermal cycle (<40 min) was devised including 5 min dwell times at temperatures in the range 900–950 °C and 1250–1300 °C, followed by 10–15 min at 1500–1550 °C. The chemical and mineralogical data of the grey clinker produced are encouraging since values of 51.0 ± 6.9% C3 S, 22.7 ± 5.3% C2 S, 8.6 ± 0.4% C3 A and 10.8 ± 0.7% C4 AF are similar to those observed for conventional clinker used for the production of Portland cement in accordance to EN 197-1 standard. White clinker, in turn, could not be produced by direct irradiation in this setup conditions because of its low absorptance of solar energy.